Kasih dan Keadilan Allah Berdasarkan Amos 2:6-16 - Prissila, Amita (Jurnal Kala Nea, 2024)
God justice is evident in the actions, laws, and even punishment that God gives to sinful humans. Humans must obey God by not committing evil acts. God will enforce justice against humans who do evil. Amos 2:6 explains that the Israelites had sinned repeatedly, causing God to punish Israel. Therefore, the purpose of this research is to find out an exegetical understanding of God justice based on Amos 2:6-16 which can be implied in the attitude of life of believers not to do evil deeds in the eyes of God. In writing this article, the author used a library research research method (Library Research) with a descriptive qualitative approach by interpreting (hermeneutics), exegesis (digging the Bible) and exposition (explaining the purpose and purpose of the text). The results of research on God's Justice Based on Amos 2:6-16 explain that God punished Israel for sinning against God. Israel sold the righteous and the poor for money, led the poor astray, committed adultery, rejected the prophet who conveyed God law. As people who believe in God, humans must obey and not commit sins against God. Do not sell the righteous and poor for money, do not lead the poor astray, do not commit adultery, do not serve God, and do not forget the goodness of God in life that brings salvation.